Digital Terrain Model Data Structures - Abdul Rahman, Alias (Fakulti Ukur dan Harta Tanah, 1994)
This paper describes pertinent digital terrain model data structures, namely, grid/raster, quadtree, and triangular irregular network. A basic concept of DIM data structure is also explained. The aspects of TIN storage, TIN data structure conversion, advantages and disadvantages of each structure are discussed. A complete data structure conversion program is also presented.